Canonical and Novel Non-Canonical Cholinergic Agonists Inhibit ATP-Induced Release of Monocytic Interleukin-1β via Different Combinations of Nicotinic Acetylcholine Receptor Subunits α7, α9 and α10 - Zakrzewicz, Anna; Richter, Katrin; Agné, Alisa; Wilker, Sigrid; Siebers, Kathrin; Fink, Bijan; Krasteva-Christ, Gabriela; Althaus, Mike; Padberg, Winfried; Hone, Arik J.; McIntosh, J. Michael; Grau, Veronika (Frontiers in Cellular Neuroscience, 2017)
Recently, we discovered a cholinergic mechanism that inhibits the ATP-dependent release of interleukin-1β (IL-1β) by human monocytes via nicotinic acetylcholine receptors (nAChRs) composed of α7, α9 and/or α10 subunits. Furthermore, we identified phosphocholine and dipalmitoylphosphatidylcholine as novel nicotinic agonists that elicit metabotropic activity at monocytic nAChR. Interestingly, phosphocholine does not provoke ion channel responses at conventional nAChRs composed of subunits α9 and α10. The purpose of this study is to determine the composition of nAChRs necessary for nicotinic signaling in monocytic cells and to test the hypothesis that common metabolites of phosphatidylcholines, lysophosphatidylcholine and glycerophosphocholine, function as nAChR agonists. In peripheral blood mononuclear cells from nAChR gene-deficient mice we demonstrated that inhibition of adenosine triphosphate (ATP)-dependent release of IL-1β by acetylcholine, nicotine and phosphocholine depends on subunits α7, α9 and α10. Using a panel of nAChR antagonists and siRNA technology we confirmed the involvement of these subunits in the control of IL-1β release in the human monocytic cell line U937. Furthermore, we showed that lysophosphatidylcholine (C16:0) and glycerophosphocholine efficiently inhibit ATP-dependent release of IL-1β. Of note, the inhibitory effects mediated by lysophosphatidylcholine and glycerophosphocholine depend on nAChR subunits α9 and α10, but only to a small degree on α7. In Xenopus laevis oocytes heterologously expressing different combinations of human α7, α9 or α10 subunits, acetylcholine induced canonical ion channel activity, whereas lysophosphatidylcholine, glycerophosphocholine and phosphocholine did not. In conclusion, we demonstrate that canonical nicotinic agonists and phosphocholine elicit metabotropic nAChR activity in monocytes via interaction of nAChR subunits α7, α9 and α10. For the metabotropic signaling of lysophosphatidylcholine and glycerophosphocholine, nAChR subunits α9 and α10 are needed, whereas α7 is virtually dispensable. Furthermore, molecules bearing a phosphocholine group in general seem to regulate immune functions without perturbing canonical ion channel functions of nAChR.